Attenuation of Radiation-Induced Lung Injury by Hyaluronic Acid Nanoparticles - Lierova, Anna; Kasparova, Jitka; Pejchal, Jaroslav; Kubelkova, Klara; Jelicova, Marcela; Palarcik, Jiri; Korecka, Lucie; Bilkova, Zuzana; Sinkorova, Zuzana (Frontiers in Pharmacology, 2020)
Purpose: Therapeutic thorax irradiation as an intervention in lung cancer has its limitations due to toxic effects leading to pneumonitis and/or pulmonary fibrosis. It has already been confirmed that hyaluronic acid (HA), an extracellular matrix glycosaminoglycan, is involved in inflammation disorders and wound healing in lung tissue. We examined the effects after gamma irradiation of hyaluronic acid nanoparticles (HANPs) applied into lung prior to that irradiation in a dose causing radiation-induced pulmonary injuries (RIPI). Materials and methods: Biocompatible HANPs were first used for viability assay conducted on the J774.2 cell line. For in vivo experiments, HANPs were administered intratracheally to C57Bl/6 mice 30 min before thoracic irradiation by 17 Gy. Molecular, cellular, and histopathological parameters were measured in lung and peripheral blood at days 113, 155, and 190, corresponding to periods of significant morphological and/or biochemical alterations of RIPI. Results: Modification of linear hyaluronic acid molecule into nanoparticles structure significantly affected the physiological properties and caused long-term stability against ionizing radiation. The HANPs treatments had significant effects on the expression of the cytokines and particularly on the pro-fibrotic signaling pathway in the lung tissue. The radiation fibrosis phase was altered significantly in comparison with a solely irradiated group. Conclusions: The present study provides evidence that application of HANPs caused significant changes in molecular and cellular patterns associated with RIPI. These findings suggest that HANPs could diminish detrimental radiation-induced processes in lung tissue, thereby potentially decreasing the extracellular matrix degradation leading to lung fibrosis.